Oral health and liver function in children and adolescents with cirrhosis of the liver - Olczak-Kowalczyk, Dorota; Kowalczyk, Wojciech; Krasuska-Sławińska, Ewa; Dądalski, Maciej; Kostewicz, Krzysztof; Pawłowska, Joanna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction: People with cirrhosis of the liver are predisposed to developing oral lesions. The occurrence and type of lesion depend on the degree of liver function impairment and its type, and on the severity and duration of systemic diseases. In children, the age at which the early symptoms of liver disease are experienced is also of great importance. Aim : To assess the prevalence of oral pathological lesions in children and adolescents with cirrhosis of the liver, and their correlation with the degree of liver function impairment. Material and methods: Clinical and laboratory results of liver function tests (Model of End-Stage Liver Disease/Score of Paediatric End-Stage Liver Disease, Child-Pugh score) were assessed in 35 patients with cirrhosis of the liver. The average age of the patients was 10.7 ±4.74 years. All patients also had their oral cavities examined (mucosa, gingiva – GI, hygiene – PLI, teeth – dmft/dmfs and DMFt/DMFs, DDE Index and Candida spp. presence) and this was then correlated to the degree of liver function impairment. Results : According to the Child-Pugh scale, 16 patients were class A and 19 were class B/C. Jaundice during the first 3 years of life occurred in 9 patients. Mucosal lesions were found in 26 out of 35 patients (74%), including 10 out of 16 (63%) in Child-Pugh group A, and 16 out of 19 (84%) in group B/C (NS – non significant). Oral candidiasis occurred more often in class B/C than in class A (47.4% vs. 12.5%; p < 0.05). The GI index (Gingival Index) and PLI index (Dental Plaque Index) did not differ between the groups (A vs. B/C) but correlated in the whole group (R = 0.58) as well as in subgroups A (R = 0.65) and B/C (R = 0.59). Dmft/dmfs and DMFt/DMFs indexes did not differ between groups A and B/C, and neither did the DMFt/DMFs in patients with/without enamel defects. Conclusions: Oral mucosal lesions are commonly found in children with cirrhosis of the liver. Advanced liver disease promotes oral candidiasis. Severity of gingivitis correlates with the presence of dental plaque.